Short term panic intervantion, a pilot study - Sigurbjörg Sigurpálsdóttir 1981- (2017)
Panic Disorder (PD) is an anxiety disorder characterized by sudden and unexpected panic attacks. Research has shown that cognitive behavioural therapy (CBT) is an effective treatment for PD. A brief treatment program called Short Term Panic Intervention (STPI) is offered at the Emergency Ward of the Mental Health Division at Landspitalinn-The National University Hospital of Iceland. The STPI consists of four 60-minute treatment sessions. The treatment utilizes the main treatment methods of CBT for PD such as cognitive restructuring, minimizing safety-seeking behaviours, behavioural experiments and correcting misinterpretations of physical symptoms. Participants were consenting patients who came to the Emergency Ward and were referred to the treatment by health-care professionals. The treatment consisted of a psychoeducation session followed by up to three discussion sessions. The aim of the study was to test if the treatment lead to reduced frequency of panic attacks and decreased anxiety symptoms in general. Participants were 19 adults between the age of 18 and 55, of whom 79% were women. Nearly half of the participants (47%) had no panic attacks during the week before post-treatment assessment. Results show a statistically significant decrease on all measures used in the study. Results also show that 32 – 47 % of the participants experienced reliable improvement on anxiety and depressive symptoms post-treatment. Results indicate that there are some improvements for those who suffer from panic attacks after participating in the STPI treatment. Complete experimental control was not possible, therefore determining whether the STPI was the main cause of change is difficult to say. Keywords: panic disorder, cognitive behavioural therapy, brief treatment, group treatment